2019
DOI: 10.1038/s41598-019-39824-9
|View full text |Cite
|
Sign up to set email alerts
|

Depiction of Oral Tumor-Induced Trigeminal Afferent Responses Using Single-Fiber Electrophysiology

Abstract: Considerable gap in knowledge exists about the mechanisms by which oral tumors regulate peripheral sensory fibers to produce pain and altered sensations. To address this gap, we used a murine model of oral squamous cell carcinoma (OSCC) of the tongue to investigate changes in response properties of trigeminal afferent neurons. Using this model, we developed an ex vivo method for single neuron recordings of the lingual nerve from isolated tongue tissue. Our data demonstrated that the tongue tumor produced incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…In addition, due to the relatively small sample size that is feasible to achieve with microneurography, these rare units may not have been captured. One previous study recorded pressure-response dynamics in tongue-innervating mechanosensory neurons using mouse tongue-nerve preparations (Grayson et al, 2019). This study found that high-threshold mechanoreceptors were the most abundant class present in the tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to the relatively small sample size that is feasible to achieve with microneurography, these rare units may not have been captured. One previous study recorded pressure-response dynamics in tongue-innervating mechanosensory neurons using mouse tongue-nerve preparations (Grayson et al, 2019). This study found that high-threshold mechanoreceptors were the most abundant class present in the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of these mechanosensory terminals are distinct from Piezo2-positive afferents in skin and other tissues; therefore, their functions in sensation are unknown. Previous electrophysiological studies identified a variety of physiological types of neurons innervating the tongues humans, cats and mice (Biedenbach & Chan, 1971; Grayson et al, 2019; Robinson, 1992; Smith & Robinson, 1995; Trulsson & Essick, 1997, 2010). In humans and cats, the majority of tongue mechanoreceptors are rapidly adapting, a typical property of Meissner corpuscles, indicating that the tongue is tuned for the detection of moving stimuli (Biedenbach & Chan, 1971; Mountcastle et al, 1967; Robinson, 1992; Trulsson & Essick, 1997, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aδ polymodal nociceptors are rare in the skin but enriched in visceral afferents [ 21 ]. A recent study has also shown the characteristics of afferents innervated to the tongue in mice [ 22 ]. Approximately 50% of lingual afferents are c fibers, while approximately 30% are Aδ fibers.…”
Section: Physiological Somatosensation and Pain From Oral Mucosa And Facial Skinmentioning
confidence: 99%
“…Approximately 50% of lingual afferents are c fibers, while approximately 30% are Aδ fibers. In this study, the implantation of oral squamous carcinoma into the tongue increased spontaneous firing, decreased the mechanical thresholds of the c and Aδ mechanoreceptors, and reduced the proportion of mechanically insensitive fibers [ 22 ].…”
Section: Physiological Somatosensation and Pain From Oral Mucosa And Facial Skinmentioning
confidence: 99%
See 1 more Smart Citation